Selection criteria predictive of academic success in the first two years of the integrated diploma in nursing - L. R. Uys (AOSIS, 1993)
Student wastage during basic nursing programmes has been estimated at between 20% and 47% per annum over the last 10 years (Kotze, 1987; SANA, 1983). The training of every student costs the state approximately R13 500 per annum according to an investigation done by the SA Nursing Association in 1987. The economic loss due to the student wastage is therefore significant. At the same time student numbers are declining at a time during which many more nurses are necessary to maintain the ratio of registered nurses to the population (Kotze, 1987). The student wastage therefore also has serious implications for the health services. Since training schools usually receive more applications than can be accommodated as students, the process of selection becomes a key factor in selecting students who will complete the programme and join the professional nursing cadre.